Inguinal bladder hernia with bladde calculi and renal impairment in an elderly male: A case report - Xiaojie Liu; Yun Zhang; Chao Yang (Urology Case Reports)
Inguinal bladder hernia (IBH) is a rare condition, representing less than 5 % of all inguinal hernias. We present a case of IBH with bladder calculi and renal impairment, emphasizing the role of ultrasound and CT imaging in diagnosis and management. Through this case, we discussed the clinical features and imaging findings of IBH, and mentioned ''second eye ultrasound'' in order to improve the understanding of this rare disease and the level of preoperative diagnosis and treatment.